2016
DOI: 10.1016/j.jpha.2016.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Screening primary racemic amines for enantioseparation by derivatized polysaccharide and cyclofructan columns

Abstract: It is a challenge to separate the enantiomers of native chiral amines prone to deleterious silanol interactions. A set of 39 underivatized chiral primary amines was screened for enantiomeric separation. Seven recently introduced commercial chiral columns were tested. They included six polysaccharide based chiral stationary phases (CSP) with bonded derivatives, ChiralPak® IA, IB, IC, ID, IE and IF columns and a cyclofructan derivatized CSP, Larihc® CF6-P column. Both the normal phase (NP) mode with heptane/alco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…In a screening study, the enantioseparation capability of Larihc CF6-P was evaluated and compared to six polysaccharide-based CSPs applying the NP mode with n -heptane/ethanol or PO mode with acetonitrile/methanol or 2-propanol eluent systems [ 51 ]. The CF-based CSP demonstrated the highest success rate in the separation of 39 nonderivatized chiral primary amines in PO mode.…”
Section: Recent Applications Of Cyclofructan-based Cspsmentioning
confidence: 99%
“…In a screening study, the enantioseparation capability of Larihc CF6-P was evaluated and compared to six polysaccharide-based CSPs applying the NP mode with n -heptane/ethanol or PO mode with acetonitrile/methanol or 2-propanol eluent systems [ 51 ]. The CF-based CSP demonstrated the highest success rate in the separation of 39 nonderivatized chiral primary amines in PO mode.…”
Section: Recent Applications Of Cyclofructan-based Cspsmentioning
confidence: 99%
“…Thus, the bulkiness of IPA could alter the size and shape of the helical grooves to become more favorable for The above results indicated that the branched alcohol (IPA) has a higher ability to modify the steric environment in chiral grooves of the amylose polymeric backbone, which likely seems to be correlated with the high steric size of IPA. Thus, the bulkiness of IPA could alter the size and shape of the helical grooves to become more favorable for enantioseparation [18]. Therefore, the reason for the enantioselectivity on Chiralpak AD−3 strongly relies on the modification of chiral grooves that lets portions of the closantel enantiomers enter and exhibit interactions with the active part of the polymer.…”
Section: The Effect Of the Nature And Proportion Of Alcohol Modifiers On The Enantiomeric Separation Of Closantelmentioning
confidence: 99%
“…To date, few studies have investigated the chiral separation of closantel enantiomers using HPLC [ 14 ]. This research aimed to develop analytical separations of closantel enantiomers using the normal-phase (NP) HPLC mode with different types of chiral selectors such as tris carbamates of amylose polysaccharides [ 15 , 16 ], isopropyl carbamates of cyclofructans [ 17 , 18 , 19 ], and β-cyclodextrins derivatives [ 20 ]. Filling the gap in the analytical separation of racemic drugs has great significance for the chemical, pharmaceutical, and biological fields.…”
Section: Introductionmentioning
confidence: 99%
“…have also been determined, especially in commercial products or biological samples (pharmaceutical formulations, human urine, human or animal blood, human plasma, animal serum, etc.). Another heterogeneous group of analytes, including connectors for building metal-organic frameworks [116,117,124], intermediates for the synthesis of pharmaceuticals [111], natural and synthetic compounds [39,113,121,120], biological compounds [82,112,58,71,78,86,[61][62][63]77,75], natural alkaloids [121], biomolecules [115,54], organometallic compounds [119] and chiral metabolites [103,108,100,97,102,59,63,52] has been enantioseparated with these immobilized polysaccharides CSPs (see Table 2-4). Fig.…”
Section: Accepted Manuscriptmentioning
confidence: 99%